THE ISSUES OF ELABORATION OF NEW DISCIPLINES FOR MASTER PROGRAM STUDENTS IN TRANSLATION STUDIES - Zhumabekova, Aigul; Mirzoyeva, Leila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of the study is to determine the structure and content of the University course "Modern Trends in Translation Studies" for MA students in translation studies.The authors propose the following structure of new course including both historical and theoretical parts: 1. History of translation in English-speaking countries (20-21 centuries); 2. History of translation in CIS (20-21 centuries); 3.History of translation in Kazakhstan; 4. Approaches to translators’ activity: Eurocentric and traditional “Soviet” approach.The second, methodological part of the course includes the following problems in translation studies: 1. Translation mechanisms (Western approach and Soviet tradition); 2. Basic translation strategies (Western and Soviet translators’ viewpoints); 3."Stumbling blocks" in contemporary translation (practical approach); 4.Main types of translation errors.The third part of the course should be rather practical, aimed at the development of translation skills on the material of three languages.